ADAPTASI SOSIAL BENTOR KONVESIONAL DI TENGAH PERSAINGAN DENGAN TRANSPORTASI ONLINE MAXIM (STUDI PENELITIAN DI AREA PANGKALAN BENTOR CITIMALL GORONTALO) - Nur Indah Hasan; Sahrain Bumulo; Sainudin Latare (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This study aims to analyze the social adaptation of conventional bentor drivers at the Citimall terminal, Heledulaa Selatan Village, Gorontalo City, in facing competition with Maxim online transportation. This research employed a descriptive qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation, with informants selected purposively from conventional bentor drivers who are actively operating in the terminal area. The results indicate three forms of social adaptation undertaken by bentor drivers: active adaptation, including seeking passengers by patrolling, reducing fares, maintaining relationships with regular customers, and utilizing social media; passive adaptation, demonstrated by remaining at the terminal without innovating despite a decline in passengers; and integrative adaptation, manifested through mutual agreements with online transportation drivers regarding operational area restrictions and the implementation of a queuing system at the terminal to maintain social harmony. These findings highlight the importance of adaptation strategies for traditional drivers to sustain their livelihoods while fostering social harmony amid the competition with modern transportation.